The Livelihood Strategy of Rural Women through the Mechanism of Nutmeg Collecting Tradition in Negeri Booi, Central Maluku - Fibryano Saptenno; Ali Tutupoho; Hendri Dony Hahury (Budapest International Research and Critics University, 2022)
The existence of rural women has always been identified as the most vulnerable group to losing their livelihoods due to limited access to assets. This study examines the role of local institutions (traditions, local wisdom and norms) in securing the women's livelihoods. This study is done in a qualitative manner with an ethnographic approach that focuses on cultural studies in a holistic sense of social groups using the perspective of a sustainable livelihood framework. This research was conducted in negeri Booi, Saparua island, Central Maluku from July to December 2020. The informants included Raja, dusung owners, women nutmeg collectors and the village government agency. The primary data was collected through in-depth interviews, observations and focus group discussions (FGD). The results show that the livelihood strategies used by the rural communities in dealing with various livelihood vulnerabilities through the use of livelihood assets could be collaborated with local wisdom or traditions as informal insurance, so that the efforts to “save or secure” the poor from “unsafe” to “safer” conditions could be guaranteed and continued to be sustainable. In short, the local wisdom of collecting nutmeg intended for women in negeri Booi had guaranteed the sustainability of women's income sources.